Optimal entanglement distribution within a multi-ring topology - B. C. Ciobanu; T. A. Calafeteanu; A. B. Popa; R. Tătăroiu; P. G. Popescu (Scientific Reports)
Abstract Entanglement distribution networks are essential for enabling secure, reliable, and sustained communication through the future Quantum Internet. Multi-ring network topologies offer improved scalability and redundancy, but also introduce additional routing complexity for the task of efficiently distributing entanglement. This paper solves the problem of optimal entanglement distribution in multi-ring quantum network topologies. Two separate multi-ring network configurations are analyzed, one where requests can only be routed within a single ring layer, and involves a less complex node setup, and one where requests may switch ring layers when passing through the network’s nodes, at the cost of additional complexity within the nodes themselves. We propose algorithms that solve the problem of entanglement distribution in terms of optimal time needed to satisfy a set of entanglement resupply requests with given network resources, as well as the problem of optimal resources in order to satisfy a set of entanglement resupply requests within a single entanglement transmission and measurement step. We provide a comprehensive analysis of the proposed algorithms through computer simulations, which indicate that the additional complexity of a network which allows switching between ring layers brings little benefit in terms of time to serve requests, but may reduce the number of resources needed to satisfy the entanglement distribution requests in a non-blocking manner.